Responsive website for TK Aisyiyah VI Candi based on content management system wordpress - Ika Ratna Indra Astutik (Institute of Computer Science (IOCS), 2023)
In the era of Industry 4.0, all data and information are readily accessible to the public online. People increasingly rely on websites to obtain information, making websites a crucial asset for companies and institutions. At TK Aisyiyah VI Candi, information about the school is currently disseminated through banners, brochures, and social media platforms such as WhatsApp. Consequently, comprehensive information about the school, especially regarding the enrollment of new students, is not widely available. The objective of this research is to create a website to facilitate the school in delivering information to the public online. This study employs the Web Development Life Cycle Method (WDLC), consisting of several phases: 1) Feasibility, 2) Analysis Requirement, 3) Design, 4) Coding, and 5) Implementation and Maintenance. The website development utilizes the Content Management System (CMS) WordPress. The outcome of this research is a school website designed using the WDLC approach. The conclusion drawn from this study is that the Website Development life Cyle Method (WDLC) proves highly effective in developing a school website, particularly concerning the creation of school profiles, announcements, agendas, and pages dedicated to the enrollment of new students.